PEMBENTUKAN KARAKTER BERBASIS KETELADANAN - Ilham Mais; Muhammad Nawir; Hidayah Quraisy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The declining condition of character education can be seen from many irregularities such as corruption, environmental destruction, criminal acts, behavior that violates rules, lowtime discipline, and irresponsible behavior. Thus, shaping the character based on exemplary and habits is essential to be carried out, especially for students, as a basis for building civilization. The objective of this study was to identify exemplary-based characters in fifthgrade students of SD Islam Athirah 2 Makassar. This study used a qualitative approach with descriptive findings presentation techniques. Data in this research were collected through participant observation, in-depth interviews, and documentation analysis. The study results concluded that the character orders based on exemplary at grade V SD Islam Athirah 2 Makassar were divided into two. The first was exemplary intentionally, which consisted of being disciplined to be on time, being responsible, caring for the environment, and caring socially. The second was an exemplary accident, consisting of exemplary teachers applying the latest learning technology and courtesy.